Bipolar Disorder and Its Factors - Mahini, Elina Ashtari; Hosseyni, Seyedeh Asra; Ebrahimkhani, Mojtaba; Mohammadi, Mahdi; Shokri, Setayesh (Advances in Social Sciences Research Journal, 2024)
This research investigates the factors contributing to bipolar disorder in adolescents and young adults aged 13 to 23. Data: The data for this study was collected from 52 adolescents and young adults, students and individuals aged between 13 to 23 years. Non-parametric single-sample or Wilcoxon tests were used for data classification and categorization. There were 34 female and 18 male participants. The findings of this research have shown us that factors such as genetics, negative emotions (anger, anxiety, and stress), substance and alcohol use, social pressure, awareness of illness and bipolar disorder, sudden lifestyle changes, mood swings, and relationship disturbances were directly associated. Factors such as regular lifestyle habits including diet, sleep, and exercise; sudden changes in lifestyle, mood swings, sexual tendencies and irrational beliefs such as suicide, as well as difficulties in adhering to daily routines, financial resources, sudden lifestyle changes, mood swings, and bipolar disorder; sudden changes in sexual tendencies and bipolar disorders have no direct relationship.